Pengaruh Model Pembelajaran Reciprocal Teaching dan Student Facilitator and Explaining Terhadap Hasil Belajar Matematika dengan Mengontrol Kemampuan Awal Siswa - Mulyono, Dodik; Elly S., As (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
The purpose of this study is to analyze: (1) mathematics learning outcomes between students who are taught using a reciprocal teaching learning model and those who are taught using a student facilitator model and explaining, after controlling students’ initial abilities; (2) the interaction between the learning model and learning independence of mathematics learning outcomes. The research population was 30 students in each training. Data collection were performed using test questions in the form of multiple choice. This research was conducted quantitatively using quasi-experimental research method. Data analysis was performed with a 2x2 level covariance analysis technique. The results of hypothesis 1 prove that Ho was rejected with F-count = 4.47 higher than F-table (0.05; 1: 59) = 4.00. Hypothesis 2 results prove that Ho was rejected with F-count = 14.94 higher than F-table (0.01; 1: 59) = 7.08.